Ethnic minorities and their language in Hungarian county seats – the census of 2011 - Bagdi Róbert („RIK-U” Kft., 2020)
Abstract. The Hungarian government in the early 1990s recognized 13 different ethnic groups as minorities. During the last two decades, their total number has increased reaching 555,507 citizens in 2011, although according to the last two censuses the questions concerning ethnicity were not compulsory to answer. In 2011, data were collected about mother tongue and second language, and people were inquired about situations in which they use their native language. Our main aim is to analyse the national minorities in the 19 County Seats of Hungary.
https://kmf.uz.ua/wp-content/uploads/2020/09/final_1_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008119
Keywords: census; mother tongue; nationality; county seats; bilingualism